1994
DOI: 10.22358/jafs/69830/1994
|View full text |Cite
|
Sign up to set email alerts
|

Implications of fasting on the energy metabolism and feed evaluation in ruminants

Abstract: Fasting metabolism is adapted to ensure the orderly mobilization of endogenous substrates and fuel for maintaining vital activity. When no exogenous energy is consumed it gives rise to a glucose deficient condition; as a result gluconeogenesis from amino acids occurs which results in a higher excretion of N and a higher heat production. When therefore fasting metabolism is adopted as the reference level of metabolism when assessing energetic efficiency, efficiency appears higher below energy maintenance (Km) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 13 publications
4
6
0
Order By: Relevance
“…Marston (1948( ), quoted by Webster et al (1974, showed that fasting heat production depended on the level of nutrition before fasting. We have identified, in agreement with Chowdhury & Ørskov (1994), yet another reason why fasting metabolism is an inappropriate basis for measuring the utilization of nutritionally-balanced diets for ruminants, and that such measurements should be based at a level of glucose supply equivalent to approximately 5⋅5 g/kg W 0⋅75 or more daily when plasma BHB is normal. The data reported here, compared with those for sheep (Chowdhury et al 1997b), suggest that there is a species difference between cattle and sheep in glucose requirement and glucose metabolism.…”
Section: Practical Implicationssupporting
confidence: 78%
“…Marston (1948( ), quoted by Webster et al (1974, showed that fasting heat production depended on the level of nutrition before fasting. We have identified, in agreement with Chowdhury & Ørskov (1994), yet another reason why fasting metabolism is an inappropriate basis for measuring the utilization of nutritionally-balanced diets for ruminants, and that such measurements should be based at a level of glucose supply equivalent to approximately 5⋅5 g/kg W 0⋅75 or more daily when plasma BHB is normal. The data reported here, compared with those for sheep (Chowdhury et al 1997b), suggest that there is a species difference between cattle and sheep in glucose requirement and glucose metabolism.…”
Section: Practical Implicationssupporting
confidence: 78%
“…Altered levels of stearoylcarnitine, L-palmitoylcarnitine, Trp and acetylcarnitine combined with the results of serum levels of NEFA, GLU and BUN indicate that sheep switch energy sources from carbohydrates to proteins and fatty acids under the OG condition, causing poorer nitrogen utilization efficiency and extra lipolysis. For energy metabolism, a number of studies revealed lower plasma GLU and ALB, and higher urea levels of ewes under restricted nutritional conditions [40][41][42]. This phenomenon was consistent with up-regulated expression of KYNU and HAL in our previously obtained hepatic proteomics data [4].…”
Section: Discussionsupporting
confidence: 89%
“…Altered levels of stearoylcarnitine, L-palmitoylcarnitine, Trp and acetylcarnitine combined with the results of serum levels of NEFA, GLU and BUN indicate that sheep switch energy sources from carbohydrates to proteins and fatty acids under the OG condition, causing poorer nitrogen utilization efficiency and extra lipolysis. For energy metabolism, a number of studies revealed lower plasma GLU and ALB, and higher urea levels of ewes under restricted nutritional conditions [39][40][41]. This phenomenon was consistent with up-regulated expression of KYNU and HAL in our previously obtained hepatic proteomics data [4].…”
Section: Discussionsupporting
confidence: 88%